1981
DOI: 10.1177/036354658100900504
|View full text |Cite
|
Sign up to set email alerts
|

Stress reactions involving the pars interarticularis in young athletes

Abstract: A stress reaction involving the pars interarticularis of the lumbar spine was confirmed in seven young athletes with a positive technetium pyrophosphate bone scan. No pars defects were detectable on their lumbosacral roentgenograms, which included oblique views. The return to normal levels of radioactive uptake on repeat bone scans correlated closely with their clinical course. If the bony reaction is recognized early, it may heal at a subroentgenographic level and prevent the development of lumbar spondylolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
1
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(67 citation statements)
references
References 4 publications
3
62
1
1
Order By: Relevance
“…We found that 88% of our patients had one or more radiographic pars abnormalities. This is not surprising since spondylolysis occurs frequently among adolescent athletes participating in strenuous sports [20,21 ]. All patients referred for scintigraphy had persistent pain after conservative management.…”
Section: Discussionmentioning
confidence: 93%
“…We found that 88% of our patients had one or more radiographic pars abnormalities. This is not surprising since spondylolysis occurs frequently among adolescent athletes participating in strenuous sports [20,21 ]. All patients referred for scintigraphy had persistent pain after conservative management.…”
Section: Discussionmentioning
confidence: 93%
“…Most sports physicians agree that the treatment of spondylolysis should include a period of rest, with or without bracing, to allow healing, rehabilitation, and return to play when asymptomatic [7] . Actually, earlier studies published in the 1980s have shown that treatment that consists of avoiding aggravating activities and rest enabled athletes to return to pain-free competition after an average interval of 7.3 mo [8] , and that after treatment with the modified Boston brace, 78% of athletes had either excellent or good results with no pain and returned to full activity [9] . Surgical treatment is indicated in athletes with persistent pain from non-healing of the pars after a minimum of 6 mo [10] .…”
Section: Brief Articlementioning
confidence: 99%
“…Lumbar spondylolysis is a condition specific to humans because of our unique anatomical characteristic of lumbar lordosis, facilitating upright posture [3]. Clinical presentation with chronic lower back pain exacerbated by hyperlordosis and/ or twisting motions is typical [4], but spondylolysis may also develop without symptoms [5].…”
Section: Introductionmentioning
confidence: 99%